The International Years of the Quiet Sun - Minnis, C. M. (Polar Record, 1964)
“The knowledge of the world is only to be acquired in the world and not in a closet.” This advice was given by the Earl of Chesterfield to his son in 1746 and, although it was not intended as such, it could well have inspired all those geophysicists who have ever left their laboratories to make observations in the field, or who have compared the results of their own experiments with those of their colleagues in other parts of the world.